Male accessory gland inflammation, infertility, and sexual dysfunctions: a practical approach to diagnosis and therapy. (9th October 2017) - Calogero, A. E.; Duca, Y.; Condorelli, R. A.; La Vignera, S.
Summary: The role of urogenital inflammation in causing infertility and sexual dysfunctions has long been a matter of debate in the international scientific literature. The most recent scientific evidences show that male accessory gland infection/inflammation could alter, with various mechanisms, both conventional and biofunctional sperm parameters, and determine worst reproductive outcome. At the same time, the high prevalence of erectile dysfunction and premature ejaculation in patients with male accessory gland infection/inflammation underlines the close link between these diseases and sexual dysfunctions. The aim of this review was to provide the reader the basis for a correct diagnosis of male accessory gland infection/inflammation and a subsequent appropriate therapeutic approach, particularly in patients with infertility and/or sexual dysfunction.